Data on how regional climate affects habitat associations and thermal sums required for development of the Eurasian spruce bark beetle, Ips typographus - Lindman, Ly (Swedish University of Agricultural Sciences, 2023)
The data was collected for the publication "Regional climate affects habitat associations and thermal sums required for development of the Eurasian spruce bark beetle, Ips typographus".
The data includes:
1) data of ambient and internal (under the bark) temperature, which was collected with two types of data-loggers. Based on that, microclimatic variables (mean, fluctuations, and thermal sums) were calculated. Thermal sums were calculated based on 5-degree and 8.3-degree models for each developmental stage as well as thermal sum reached in particular site and shade level;
2) data of habitat characteristics, including variables measured in the fiedl (like diameter, basal area and direction of the stand) as well as variables that were not directly measured (like canopy openness was analysed from fish eye lens pictures, or regional average temperature was calculated from the data of weather stations);
3) data about the dates colonisation and development of Ips tyopgraphus. These dates allowed to specify the time frame for calculating thermal sums for different development stages, thermal sums reached etc.

The data was collected from April to September 2020 in 6 regions from southern to northern Sweden (ca 1300 km gradient). Each region consisted of 5 study sites, which were mature forest stands next to 1-2 years old clear-cut.

The dataset includes variables that are related to a) identification of loggers and logs, b) location, c) measured/calculated habitat variables, d) binary variables for colonisation and development (life stages) experiments, e) dates of the beginning and the end of colonisation as well as development experiments, f) calculated thermal sums from the data of ambient and internal loggers.

File "local_logger.csv" includes raw data collected with ambient data loggers (ambient air). The number in the first row identifies the ID number of ambient loggers. There are 3891 rows and 92 columns in the table.
File "logger.csv" includes raw data collected from internal data loggers (under the bark). The number in the first row identifies the ID number of internal loggers. There are 3890 ros and 178 columns in the table.
In the file "Ips_data.csv", the numbers of these loggers are in columns "local_logger" and "logger", repectively. There are 451 rows and 63 columns in the table.

Uppgifterna samlades in för publikationen "Regionalt klimat påverkar habitatföreningar och termiska summor som krävs för utveckling av granbarkborren, Ips typographus".
Uppgifterna inkluderar:
1) data om omgivningstemperatur och inre temperatur (under barken), som samlades in med två typer av dataloggare. Utifrån det beräknades mikroklimatiska variabler (medelvärde, fluktuationer och termiska summor). Termiska summor beräknades baserat på 5-graders- och 8,3-gradersmodeller för varje utvecklingsstadium samt termisk summa som uppnåtts på en speciell plats och skugganivå;
2) data om habitategenskaper, inklusive variabler uppmätta i fiedl (som diameter, basalarea och beståndets riktning) samt variabler som inte mättes direkt (som kapellets öppenhet analyserades från fiskögonlinsbilder eller regional medeltemperatur beräknades från data från väderstationer);
3) data om datum för kolonisering och utveckling av Ips tyopgraphus. Dessa datum gjorde det möjligt att specificera tidsramen för beräkning av termiska summor för olika utvecklingsstadier, uppnådda termiska summor etc.

Uppgifterna samlades in från april till september 2020 i 6 regioner från södra till norra Sverige (ca 1300 km lutning). Varje region bestod av 5 undersökningsplatser, som var mogna skogsbestånd intill 1-2 år gamla kalhygge.

Datauppsättningen innehåller variabler som är relaterade till a) identifiering av loggare och stockar, b) plats, c) uppmätta/beräknade habitatvariabler, d) binära variabler för kolonisering och utveckling (livsstadier) experiment, e) datum för början och slutet av koloniseringen samt utvecklingsexperiment, f) beräknade termiska summor från data från omgivande och interna loggare.

Filen "local_logger.csv" inkluderar rådata som samlats in med omgivande dataloggrar (omgivande luft). Numret i den första raden identifierar ID-numret för omgivande loggare. Det finns 3891 rader och 92 kolumner i tabellen.
Filen "logger.csv" innehåller rådata som samlats in från interna dataloggrar (under barken). Numret i den första raden identifierar ID-numret för interna loggare. Det finns 3890 ros och 178 kolumner i tabellen.
I filen "Ips_data.csv" finns numren på dessa loggare i kolumnerna "local_logger" respektive "logger". Det finns 451 rader och 63 kolumner i tabellen.
Data om hur regionalt klimat påverkar habitatföreningar och termiska summor som krävs för utveckling av granbarkborren, Ips typographus
Keywords: VEGETATION; living environment; livsmiljö; life cycle; livslängd; light; ljus; biology; biologi; life cycle; Habitats and biotopes; Naturtyper och biotoper; Species distribution; Arters utbredning; lifetime (period of time); livstid; animals; insecta; spruce bark beetle; granbarkborre; Ips typographus; Dyntaxa; Zoology; Zoologi; Ecology; Ekologi; Biota; Biologi och ekologi